Information literacy beyond library 2.0 - Godwin, Peter; Parker, Jo (Facet Publishing, 2012)
Over the years the information environment has changed dramatically, becoming increasingly dominated by the social and the mobile. This book asks where we are now, what is same and what has changed, and, most crucially, how do we as professionals respond to the new information literacy and become a central part of the revolution itself?